2021
DOI: 10.1038/s41408-021-00542-z
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide in combination with R-CHOP produces high response rates and progression-free survival in new, untreated diffuse large B-cell lymphoma transformed from follicular lymphoma: results from the Phase 2 MC078E study

Abstract: Diffuse large B-cell lymphoma (DLBCL), either concurrent with or transformed from follicular lymphoma (FL) is often excluded from clinical trials. Lenalidomide has response rates of 45% in relapsed transformed DLBCL. Herein we present an analysis of MC078E, a phase II clinical trial testing lenalidomide plus R-CHOP (R2CHOP) for patients with untreated transformed/concurrent DLBCL (NCT00670358). Adult patients with transformed or concurrent DLBCL were included. Patients received six cycles of rituximab, cycloph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…MS-LME exhibited enriched signatures from vascular endothelial cells, cancer-associated fibroblasts, fibroblastic reticular cells, and extracellular matrix, 9 all of which are linked to favorable outcome in DLBCL. 9 For IPI scores of ≥2, GC-LME, IN-LME, and DP-LME categories correlated with inferior prognosis, indicating a necessity for more precise treatment within these patients: GC-LME represented transformed variants of indolent, GC-derived follicular lymphoma, and may be sensitive to lenalidomide plus R-CHOP 9 , 41 ; IN-LME exhibited an enrichment of neutrophils, macrophages, CD8 + T cells, CD8 + T cells with high programmed cell death protein 1 expression, as well as immune-suppressive cytokines. Using Bruton tyrosine kinase inhibitors or other potential agents to modulate the immunosuppressive microenvironment could be potential therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…MS-LME exhibited enriched signatures from vascular endothelial cells, cancer-associated fibroblasts, fibroblastic reticular cells, and extracellular matrix, 9 all of which are linked to favorable outcome in DLBCL. 9 For IPI scores of ≥2, GC-LME, IN-LME, and DP-LME categories correlated with inferior prognosis, indicating a necessity for more precise treatment within these patients: GC-LME represented transformed variants of indolent, GC-derived follicular lymphoma, and may be sensitive to lenalidomide plus R-CHOP 9 , 41 ; IN-LME exhibited an enrichment of neutrophils, macrophages, CD8 + T cells, CD8 + T cells with high programmed cell death protein 1 expression, as well as immune-suppressive cytokines. Using Bruton tyrosine kinase inhibitors or other potential agents to modulate the immunosuppressive microenvironment could be potential therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The phase II MC078E study showed that lenalidomide in combination with standard frontline treatment R-CHOP produced high response rates; the ORR in the intent-to-treat population was 97% (32/33), 29 (88%) had CR, and 3 had PR [ 28 ]. In a phase I study of lenalidomide plus R-CHOP, the ORR was 90%, with 81% of untreated, elderly patients with DLBCL achieving CR [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A randomized phase II study of 64 patients treated with lenalidomide and R‐CHOP (R2CHOP) revealed an improved 24‐month PFS and OS relative to R‐CHOP among non‐GCB DLBCL 65 . Two single‐arm phase II trials also identified the potential benefits of R2CHOP in elderly patients 66,67 . However, two large phase III RCTs, ROBUST and ECOG‐ACRIN E1412, demonstrated conflicting results.…”
Section: Frontline Therapymentioning
confidence: 99%
“…65 Two single-arm phase II trials also identified the potential benefits of R2CHOP in elderly patients. 66,67 However, two large phase III RCTs, ROBUST and ECOG-ACRIN E1412, demonstrated conflicting results.…”
Section: Immunomodulatory Agentsmentioning
confidence: 99%